Mengembangkan Bahasa Indonesia Anak Usia Dini Melalui Permainan Kotak Ajaib Di Raudhatul Athfal Munzhiroh 3 Kulim Kota Pekanbaru - Nikmah, Nikmah; Inmaryanto, Inmaryanto; Elfita, Elfita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research is motivated by the lack of children's Indonesian language development, some children have not been able to recognize simple words and some children are less active in learning. The purpose of this study was to determine the improvement of children's Indonesian language skills by using the magic box game through the CAR research method (Classroom Action Research). This research was conducted in two cycles and each cycle was conducted in two meetings. In order for this classroom action research to be successful without any obstacles that interfere with the smooth running of the research, the researcher arranges the stages that are passed in classroom action research, namely: 1) Action planning/preparation, 2) Action implementation, 3) Observation, and 4) Reflection. The subjects in this study were B1 class students with 16 students, namely in the first semester of the 2022/2023 academic year at RA Munzhiroh 3 Kulim Pekanbaru City. Meanwhile, the object of this research is the use of the magic box game to improve the development of Indonesian in children. The research data were collected through teacher observation techniques and children's activities and documentation. After the data is collected through observation, the data is processed using the percentage formula. The results of this study are an increase in the learning process carried out by the teacher and the children's Indonesian language skills. Observation of children's activities also increased, this can be seen from the initial data to cycle II meeting 2. Initial data 41.27%, Cycle II meeting 2 obtained an average percentage of 85.28%. So that the overall increase in teacher activity obtained an average percentage of 44.01%